Americas Association of Sarcoidosis and other granulomatous disorders 2024 conference highlights - Mathias, Kristen; Wagle, Anjali; Dominguez-Peñuela, Susana; Pardo, Carlos; Sharp, Michelle; Gilotra, Nisha (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
The Americas Association of Sarcoidosis and Other Granulomatous Disorders (AASOG) 2024 conference, held in Baltimore, Maryland, leveraged a multidisciplinary approach to disseminating and addressing the latest updates, challenges and opportunities in multisystemic sarcoidosis. The conference, aptly titled “The Art of Working Together for Progress,” featured insights from diverse perspectives in sarcoidosis both nationally and internationally. This review summarizes the key takeaways from the six conference sessions: I. Sarcoidosis Multidisciplinary Care, II. Health Disparities in Sarcoidosis, III. The Search for Precision in Sarcoidosis, IV. Clinical Outcomes in Sarcoidosis, V. Clinical Trials in Sarcoidosis, and VI. Advanced Disease in Sarcoidosis.